Guardians of the Gut: Enteric Defensins - Sankaran-Walters, Sumathi; Hart, Ronald; Dills, Chantelle (Frontiers in Microbiology, 2017)
Enteric defensins likely play a key role in the management of the human microbiome throughout development. The functional and mechanistic diversity of defensins is much greater than was initially thought. Defensin expression and overall Paneth cell physiology likely plays a key role in the development of colitis and other inflammatory or dysbiotic diseases of the gut. As our understanding of enteric defensins grows, their potential as tools of clinical intervention becomes more apparent. In this review, we focus on the function and activity of Paneth Cell defensins and highlight their role in disease.